Leukocyte mRNA sequencing reveals unfolded protein response activation in severe heat stroke in Japan - Nomura, Yusuke; Oda, Sayaka; Matsumoto, Hisatake; Togami, Yuki; Shimazaki, Junya; Okuzaki, Daisuke; Ogura, Hiroshi; Oda, Jun (Frontiers in Cell and Developmental Biology, 2025)
BackgroundSevere heat stroke can cause multi-organ dysfunction and can be fatal, yet its underlying pathophysiology remains poorly understood. While RNA alterations are known to occur in critical illness, their specific role in severe heat stroke has not been comprehensively studied. Understanding these molecular changes may improve diagnostic and therapeutic strategies. This study aimed to investigate the pathogenesis of severe heat stroke by analyzing RNA expression profiles in Japanese patients in comparison to healthy controls.ResultsThis single-center, prospective, observational study included seven patients (median age: 69 ± 21.5 years; 57.1% male) with severe heat stroke admitted to Osaka University Hospital Emergency Center between August 2020 and July 2021, along with five healthy controls. All patients exhibited central nervous system symptoms and renal dysfunction; 28.6% had hepatic dysfunction or coagulopathy, and one patient (14.3%) died. RNA sequencing of leukocyte total RNA identified 15,876 RNAs, among which 1,106 were upregulated and 1,000 were downregulated in patients relative to controls (|log2 fold change| > 1, false discovery rate < 0.1). Pathway analysis revealed significant activation of the endoplasmic reticulum stress response, particularly the unfolded protein response, which is involved in cellular stress adaptation and survival mechanisms.ConclusionSevere heat stroke in Japanese patients was associated with widespread changes in RNA expression, highlighting activation of the endoplasmic reticulum stress response. These findings provide new insights into the pathophysiology of heat stroke and suggest that targeting cellular stress pathways may be a potential therapeutic approach. Further research is needed to validate these results in larger cohorts and assess their clinical implications.